COMBINATION OF HIGHT FLOW NASAL CANULA AND SEMI FOWLER POSITION TO INCREASE OXYGENATION WITH ACUTE LUNGS CARDIOGENIC OEDEMA - Purnamasari, Alifa Tanti; Rahmah, Syafira Aulia; Pratiwi, Indah Dwi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Acute cardiogenic lung edema is an emergency condition in which fluid accumulates in the lung cavity due to ventricular failure including blood throughout the body. The most fatal consequence of this condition is the disruption of the gas exchange process in the alveoli. One of the characteristic symptoms of this disease is shortness of breath which must be treated immediately so as not to fall into hypoxic or hypoxemic conditions. Therefore writing this paper aims to test the effectiveness of the combination of high-flow nasal cannula and semi-Fowler's position to increase oxygenation in patients with cardiogenic acute pulmonary edema. The research method used is a case report. This research was conducted for 4 days of treatment from 11-15 May 2022 at the Kanjuruhan Regional General Hospital, Malang Regency. After 4 days of action, there was a positive change in the patient's oxygenation. It can be seen from the results of monitoring SpO2 and RR on day 3 of treatment that there was an increase in SpO2 of 93% and a decrease in RR of 18x/minute which was getting better until day 4 of treatment. Problems related to oxygenation in the lungs, acute cardiogenic edema occurs due to accumulation of fluid in the lung cavity Actions that must be taken to continue to meet the need for adequate oxygenation in patients so that a combination of high-flow nasal cannula therapy and semi -Fowler's position is carried out to improve patient oxygenation. The recommendations for giving this therapy are by considering the replacement of the type of mask and the flow of oxygen given.